‘Matcha-Act’ Website as Learning Media for Linear Equation in Junior High School - Mei Dwi Jayanti; Rustanto Rahardi; Cholis Sa'dijah (PRISMA, 2026)
One of mathematic topic that often considered difficult is linear equation. This research aims to develop “Matcha-Act” website as learning media for linear equation that is both valid and practical for mathematic learning. Adopting a Research and Development (R&D) framework, the study employed ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research were 8th grade junior high school students. The data gathered via media validation instruments and response questionnaires. The result indicated that the “Matcha-Act” website were valid and achieving a score of 3.2 or 80%. Furthermore, practicality test yielded a score of 3.1 or 77.5%. It means that “Matcha-Act” website-media were practical to use. The advantages of “Matcha-Act” website media include its accessibility and convenience, an engaging and interactive interface, and its ability to assist students in discovering concepts independently under teacher guidance. Consequently, the Matcha-Act” website is verified as a valid and practical learning media, making it suitable for mathematics learning, particularly on the topic of linear equations.